Environmental regulation and corporate performance: The effects of green financial management and top management's environmental awareness - Suijun Chen; Pankaewta Lakkanawanit; Muttanachai Suttipun; He Xue (Cogent Business & Management, 2023)
Drawing from the circular economy, which prioritizes resource optimization, waste reduction, and operational efficiency, the objective of this study is to investigate the influence of environmental regulations on Green Financial Management (GFM), the role of GFM as a mediator between environmental regulations and corporate performance, and the moderating effect of Top Management's Environmental Awareness (TMEA). Using the questionnaires from 684 Chinese green enterprises, the structural equation analysis is used to verify the results. The empirical findings indicate that environmental regulation has a positive effect on GFM and that GFM acts as a mediator between environmental regulation and corporate performance. However, it is found that TMEA does not have a significant moderating effect between environmental regulation and GFM. This study contributes to the broader discussion around resource efficiency and sustainability in the circular economy by emphasizing the importance of companies complying with environmental regulations and adopting GFM strategies to improve performance. Policymakers can consider the role of GFM in promoting sustainable business development, and prioritize the development and implementation of strong environmental regulations.
Keywords: 650; Environmental regulation; corporate performance; green financial management; top management's environmental awareness